An Exploration into the Teaching of Cosmopolitan Ideals: The Case of 'Global Citizenship'. (June 2013) - Watson, Sam
This article examines why we should continue to teach based upon cosmopolitan ideals, despite the shortfalls of global citizenship as a concept. The author first defines and critically engages with both cosmopolitanism and global citizenship, before identifying where these concepts originate from and tracking their progression throughout time. The article then discusses the different views and values attached to each of these concepts, aiming to distinguish what differences there are between the two. Simultaneously, the author uses examples both from academic literature and his own experiences to date in order to place the theory of these two concepts within the context of modern-day life. Ultimately, however, the author argues to highlight the practical differences which separate cosmopolitan ideals and global citizenship as a concept, concluding that global citizenship fails to take our local context into account, and thus serves as a contradiction to our immediate epistemologies.